IMPROVING STUDENTS ABILITY IN SPEAKING ABOUT ASKING AND GIVING OPINION THROUGH GUIDED CONVERSATIONS - Randong, Flaurensia Agustine; Marbun, Rismaya; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Improving Students Ability in Speaking about Asking and Giving Opinion through Guided Conversations is a Classroom Action Research at Eighth Grade B Students of SMP N 21 Terpadu Pontianak in Academic Year 2011/2012. The aim of this research is to know how guided conversations improve students ability in speaking about asking and giving opinion. The researcher used classroom action research as the method of this research. Based on the analysis of the students test result, the writer describes the qualification of students mean score in second cycles (70.8) which reached 100% of achievement score is Good to Excellent. Key Word: speaking, asking and giving opinion, guided conversations Abstrak: Meningkatkan Kemampuan Siswa dalam Berbicara mengenai Meminta dan Memberikan Pendapat menggunakan Percakapan-percakapan Terpandu adalah sebuah Penelitian Tindakan Kelas pada Siswa Kelas Delapan B di SMP N 21 Terpadu Pontianak Tahun Ajaran 2011/2012. Penelitian ini bertujuan untuk mengetahui bagaimana percakapan-percakapan terpandu meningkatkan kemampuan siswa dalam berbicara mengenai meminta dan memberikan pendapat. Peneliti menggunakan penelitian tindakan kelas sebagai metode dalam penelitian ini. Berdasarkan analisa pada hasil test siswa, penulis menyimpulkan bahwa kualifikasi nilai rata-rata siswa pada putaran kedua (70,8) yang mana mencapai nilai ketuntasan 100% dikategorikan Good to Excellent. Kata Kunci: berbicara, meminta dan memberikan pendapat, percakapan-percakapan terpandu